2014
DOI: 10.3349/ymj.2014.55.6.1473
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic Evaluation of Immediate Hypersensitivity to Cefaclor

Abstract: PurposeCefaclor is widely prescribed for various infectious diseases. As its consumption increases, the number of hypersensitivity reactions to cefaclor has increased. This study aimed to evaluate the immunologic findings of immediate hypersensitivity to cefaclor.Materials and MethodsWe enrolled 47 patients with immediate hypersensitivity to cefaclor from Ajou University Hospital and Asan Medical Center. Serum specific IgE, IgG1, and IgG4 antibodies to cefaclor-human serum albumin (HSA) conjugate were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 53 publications
(83 reference statements)
2
12
0
Order By: Relevance
“…The incidence of ranitidine‐induced anaphylaxis was 3.6 times higher than the incidence reported in a previous study . There is a possibility that the incidence has increased over time, similar to cefaclor anaphylaxis . The study was based on a self‐reported database that may have underestimated the true incidence in Korea.…”
Section: Discussionmentioning
confidence: 83%
“…The incidence of ranitidine‐induced anaphylaxis was 3.6 times higher than the incidence reported in a previous study . There is a possibility that the incidence has increased over time, similar to cefaclor anaphylaxis . The study was based on a self‐reported database that may have underestimated the true incidence in Korea.…”
Section: Discussionmentioning
confidence: 83%
“… 8 11 Compared with a lower sensitivity (36.2%) for detecting serum sIgE to cefaclor-albumin conjugate by homemade ELISA, ImmunoCAP has been found to show a higher sensitivity (89.4%) for detecting cefaclor allergy at a cut-off value of 0.35 kU/L. 7 …”
Section: Discussionmentioning
confidence: 99%
“…Skin testing and measurement of serum-specific IgE (sIgE) levels to cefaclor have been well documented. 3 5 6 7 Skin testing is the primary diagnostic method, although, in patients with a history of severe reactions, in vitro tests may be recommended.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two main allergic responses are urticarial and anaphylaxis [3]. Many serum sickness type reactions to cefaclor have been reported [4,5]. Patients administered cefaclor had a higher frequency of serum sickness type reactions and urticaria than those prescribed amoxicillin [6].…”
Section: Introductionmentioning
confidence: 99%